2021
DOI: 10.5937/ekopolj2102389l
|View full text |Cite
|
Sign up to set email alerts
|

Traditional food products vs. global economy: Consumer perspective

Abstract: The Osijek-Baranya County at the East part of Croatia, generally is known as lowland region in whose economy agriculture and food industry are of great importance. Eastern Croatia abounds in various traditional products, mainly based on smoked pork. The goal of this paper is to identify consumers' attitudes and behavior towards East Croatia traditional food products (TFP). Furthermore, the model for market power evaluation of each East Croatia TFP is created according to consumers¨ preferences and attitudes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The number of gangs which is served at 'salash' is at the pleasure of participants and they all agreed that they ate and drank very well at 'salash'. Certain researchers concluded that traditional food is something people love and always return to (Lončarić et al, 2021), and 'salash' itself is a place where traditional dishes are served. Primarily this also means a traditional way of serving food is respected, which means several gangs (small dishes), from appetizer to dessert.…”
Section: Resultsmentioning
confidence: 99%
“…The number of gangs which is served at 'salash' is at the pleasure of participants and they all agreed that they ate and drank very well at 'salash'. Certain researchers concluded that traditional food is something people love and always return to (Lončarić et al, 2021), and 'salash' itself is a place where traditional dishes are served. Primarily this also means a traditional way of serving food is respected, which means several gangs (small dishes), from appetizer to dessert.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, adherence to the traditional Mediterranean diet was found to increase in Spain during the pandemic (Rodríguez-Pérez et al. , 2020), and Lončarić et al . (2021) found people of East Croatia retained a positive attitude toward traditional food products.…”
Section: Modern Theories: Consumer Culturementioning
confidence: 99%